Changing the model of radiography practice in the UAE: A snapshot of a profession in transition. Issue 1 (February 2021) - Abuzaid, M.M.; Elshami, W.; McConnell, J.; Baird, M.
Abstract: Introduction: This study forms part of a needs assessment in relation to the challenges United Arab Emirates (UAE) radiographers face as they move beyond the role of a technician, and their learning needs to facilitate role advancement. It presents a snapshot of the workforce in terms of qualifications, clinical experience, and responsibilities, as it transitions towards an Emirati, led profession. The results will aid the radiography workforce to embrace a broader role within medical imaging and radiographic practice in the UAE. Methods: An electronically distributed cross-sectional study was conducted among radiographers in the UAE. The questionnaire captured radiographer demographics, qualifications, professional experience, postgraduate training, professional development plans, and their interest in future role developments. Results: 272 radiographers were invited to participate with a response rate of 68% (n = 185). Thirty-four (18%) radiographers were UAE nationals with the remainder educated overseas. BSc qualifications were held by 153 (82.7%) and had 6–20 years of experience. There were 12 masters' qualified and two with doctoral qualifications. Modality vendors were significant providers of professional development. Improved job satisfaction and the development of an Emirati led radiography profession were identified as the main gains for role advancement by 171 (92.4%) respondents. Conclusion: Currently, UAE radiographers work within traditional professional boundaries focussing on image acquisition under direct radiologist supervision. At the same time, many respondents revealed they had embraced advanced practice roles after appropriate education and training. Implications for practice: The findings suggest an Emirati led profession requires the creation of a distinct professional body to represent the interests of radiographers, more investment in postgraduate education, and the creation of a career structure that encompasses positive role development.